Jurnal Sistem Informasi Pengepul Getah Karet Berbasis Website Di Kab Kampar - Alsha Nadia Alfara; Safni Marwa; Emon Azrialdi (Jurnal Inovasi Teknik Informatika, 2024)
As one of the plantation products in Kampar District, rubber production experienced a decrease of 13,579 tons from 2021 to 2022. Rubber tree sap or latex is a rubber raw material that is used to make various types of necessities such as: vehicle tires, fasteners, and so on. Rubber latex production is spread across several areas in Riau Province, one of which is Kampar Regency. In Kampar, the process of selling rubber latex is still done manually. Many collectors in Kampar Regency still use a book recording system, making it difficult to convey information. This becomes an obstacle for collectors where they will have difficulty estimating/recording the amount of sap/transactions. The aim of this research is to have a data collection information system for collectors to manage their businesses and customers and to make it easy for farmers to find out updates on rubber latex prices from collectors. In this research, the waterfall model SDLC development method was used. The system design uses Unified Modeling Language (UML) for the process and is implemented using the PHP programming language, Laravel Framework and MySQL database. The result is an information system to manage data for collectors in Kampar District.